Personální marketing v řízení lidských zdrojů - Myslivcová, Světlana (Masaryk University Press, 2019)
Title in English: Personal marketing in management of human resources Personnel marketing is currently taking shape as a separate industry that connects the management of human resources with marketing and places each employee into the role of a customer. The connection of these two areas creates an effect with synergy, which leads to better work with human capital. However, even despite the current need for innovative approaches to acquiring employees, the potential of personnel marketing is unsatisfactorily utilised both in the Czech Republic and abroad. In professional and scientific literature, foreign and mainly domestic, there are very few publications focused on personnel marketing comprehensively. They have explained its innovativeness, how activities carried out in personnel marketing differ from "classic" personnel-related activities. What is the relationship between personnel marketing and the employer's brand. It is synonymous, or building the brand is part of the communication strategy. Something else unknown relating to personnel marketing is its practical use. In Czech and world literature there is a lack of information about reality if practical application of personnel marketing is tied to an enterprise's size. It is also possible in connection with personnel marketing to state critically that in both professional and scientific literature, there are rarely models available which illustrate factors leading to job satisfaction. In the terminology of personnel marketing these are factors of internal personnel marketing. Models which would currently illustrate factors of external marketing and/or enable understanding of personnel marketing as a whole were not identified by the author. The main objective of the monograph was to define tools and attributes of external and internal personnel marketing and resources supporting employees' satisfaction and stability, which are important for effective management of human resources. In order to achieve this objective, quality research was conducted, along with two mutually corresponding quantitative studies - pre-research and main research. The aim of the qualitative research was to find out whether business practice is familiar with personnel marketing and how it perceives the contents of personnel marketing and to identify tools of internal and external personnel marketing applied in practice. The outputs of the qualitative research were the basis and source for realisation of quantitative research studies. Quantitative research was carried out in two steps. The pre-research research was focused on the most important employers in the Liberec Region, and the respondents were experts in human resources from these companies. The aim was to determine the perception of personnel marketing, determine the numerousness and effectiveness of personnel marketing tools, to determine the importance of individual resources for stabilisation/satisfaction of employees. Based on the results of this quantitative research, it was not possible to determine whether application of personnel marketing was tied to the company's size. Therefore, the main quantitative research was conducted. The main quantitative research was based on findings of pre-research and was focused all on employers in the Liberec Region. The respondents were HR experts from these companies. The aim was to determine the perception of personnel marketing, along with determination of the frequency of use and the importance of personnel marketing tools and to determine the degree of importance of resources that would lead to satisfaction/stabilisation of employees. The aim of the finding was also to determine whether the size of the company had an effect on individual responses. For example, an effort was made to determine if the importance of individual personnel marketing tools varied depending on company size. Also within this research, personnel marketing factors were identified, including factors that sup